Local Economic Development: A Test for Relevance in South Africa - Plaatjie, Sebeka Richard; Plaatjie, Sebeka Richard (Journal of Economics and Behavioral Studies, 2018)
The contemporary discourse on local economic development (LED) has gained widespread popularity in the political, intellectual, and public social arenas of development issues. It has become a â€œnew,â€ glittering philosophy for development. Through the persuasive use of romanticism, LED has managed to achieve moral high ground in development, although it has since been confronted by unresolved theoretical and ideological tensions. The challenges facing LED are (1) the meaning of â€œlocalâ€ in LED in a â€œglobalizedâ€ world (2) the meaning of â€œdevelopmentâ€ in LED in a democratic, multicultural and racialized class society like South Africa, and (3) the explanation and moral justification as to what this â€œdevelopmentâ€ is, or whom it should be aimed at, in a society with such a grotesquely racialized â€œpastâ€. By drawing on the findings from a recent study of LED within the Ekurhuleni Aerotropolis project, in South Africa, we provide a critique of LED. We highlight its illusive philosophical foundations and their underlying mischief in South Africa. We argue that unless the said tensions are resolved, LED discourse will remain a rhetorical ploy for legitimating underdevelopment for blacks, and a methodical device to entrench the racialized socio-economic evils of apartheid in South Africa.